The Utilization of Instagram and Tiktok as Promotion Media for Native Papuan Entrepreneurs in Jayapura - El Shaddai Sandhy Pustap; Markus Setiawan Soumokil; Hendra Litamahaputty (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Social media has become an effective marketing tool for Micro, Small, and Medium Enterprises (MSMEs). However, native Papuan entrepreneurs in Jayapura face challenges in promoting their local products due to limited digital literacy and internet access. This community service activity aimed to analyze and implement promotion strategies using Instagram and TikTok to increase the visibility of native Papuan businesses. The methods used included digital marketing training, creative content production based on local culture, and evaluation of social media engagement. The partners involved were "Roti Bakar Khas Nabire" in Jayapura City and "Sagu Bakar SAMARASTA" in Jayapura Regency. The results showed a significant increase in visibility; Roti Bakar Nabire achieved 247,582 views on Instagram and 229,414 on TikTok, while Sagu Bakar SAMARASTA reached 231,757 views on Instagram and 198,841 on TikTok. In conclusion, the utilization of short video content on social media effectively expands market reach and increases brand awareness for local Papuan products.